In the quick : a novel - Day, Kate Hope (Random House, 2021)
"In the Quick is the story of June, a brilliant but difficult girl, unloved by her adoptive family, with a gift for mechanical invention, who leaves home to begin a grueling astronaut training program. Six years later, she has gained a coveted post as an engineer on a space station, but is haunted by the mystery of Inquiry, a revolutionary spacecraft powered by her beloved late uncle's fuel cells. The spacecraft went missing when June was twelve years old, and while the rest of the world has forgotten them, June alone has evidence that makes her believe the crew is still alive. She seeks out James, her uncle's former protégée, also brilliant, also difficult, who has been trying to discover why Inquiry's fuel cells failed. James and June forge an intense intellectual bond that becomes an electric attraction. But the love that develops between them as they work to solve the fuel cell's fatal flaw threatens to destroy everything they've worked so hard to create--and any chance of bringing the Inquiry crew home alive. Equal parts gripping narrative of scientific discovery and charged love story, In the Quick is an exploration of the strength--and limits--of human ability in the face of hardship, and the costs of human ingenuity. Its beating heart is its two central characters, June and James, whose love for each other is eclipsed only by their drive to conquer the challenges of space travel"--